2009
DOI: 10.1038/ng.410
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies variants at 9p21 and 22q13 associated with development of cutaneous nevi

Abstract: High number of melanocytic nevi is the most important known risk factor for cutaneous melanoma. We conducted a genome-wide association study for nevus count using 297,108 tagSNPs in 1,524 twins and validated our results in an independent cohort of 4,107 subjects. We NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author Manuscript identified strongly associated variants in MTAP, a gene adjacent to the familial melanoma susceptibility locus CDKN2A on 9p21 (rs4636294, P = 3.4 × 10 -15 ). We further ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(215 citation statements)
references
References 28 publications
8
205
2
Order By: Relevance
“…66 Even though this would suggest a functional link, the underlying mechanism is currently unknown. Other GWASs for amyotrophic lateral sclerosis, 67 cutaneous nevi, 68 and melanoma 69 showed significant associations at Chr9p21, but the top hits were completely outside the cardiovascular risk region and the INK/ARF locus plotted in Figure 1, speaking against a functional relationship.…”
Section: Gwass Of Noncardiovascular Phenotypes and Chr9p21mentioning
confidence: 99%
“…66 Even though this would suggest a functional link, the underlying mechanism is currently unknown. Other GWASs for amyotrophic lateral sclerosis, 67 cutaneous nevi, 68 and melanoma 69 showed significant associations at Chr9p21, but the top hits were completely outside the cardiovascular risk region and the INK/ARF locus plotted in Figure 1, speaking against a functional relationship.…”
Section: Gwass Of Noncardiovascular Phenotypes and Chr9p21mentioning
confidence: 99%
“…For an extensive review on genetic loci that confer melanoma risk, including those involved in pigmentation, see Tsao et al [3]. DNA polymorphisms in nonpigmentation genes have also been associated with melanoma risk or the development of cutaneous nevi, including VDR [74], MYH7B, PIGU, TP53INP2, NCOA6, GGTL3, ACSS2, GSS, E2F1 [71], ATM, MX2, CASP8 [75], ARNT, SETDB1 [75,76], NID1 [77], PLA2G6 [78], CDK10, and FANCA [79]. Many of these non-pigmentation genes are physically close to the pigmentation genes, questioning the exact identities of the causal genes.…”
Section: Skin Cancer: Color and Environment Togethermentioning
confidence: 99%
“…Candidate gene approaches and Genome-Wide Association Studies (GWAS) have identified several lowpenetrance susceptibility genes including MC1R (55, 56), OCA2 (57-59), ASIP, TYR, SLC45A2, and TRYPT1 (60, 61) that are associated with pigmentary traits, and MTAP and PLA2G6 that are associated with the development of nevi (62,63). These higher prevalence/lower penetrance polymorphisms, which may interact with environmental exposures, are relevant to a much larger proportion of the melanoma population than the small number of familial cases caused by low-prevalence/ high-penetrance mutations in CDKN2A, ARF, and CDK4.…”
Section: Familial Melanomamentioning
confidence: 99%